Inmigración y delincuencia - Martínez, Ramiro (Revista Española de Investigación Criminológica, 2004)
The connection between immigration and crime is one of the most contentious topics in contemporary society. These discussions are not new, as debates on the issue date back more than 100 years. A general point on which both pro- and anti-immigration writers agree is that, as we enter the new millennium, the latest wave of immigration is likely to have a more important impact on society than any other social issue. In this essay, we survey the vast body of theoretical and empirical works on the relationship between immigration and crime in 20th-century America. Throughout, we include new writings as well as older, sometimes neglected works. We discuss three major theoretical perspectives that have guided explanations of the immigration/crime link: opportunity structure, cultural approaches, and social disorganization. We also examine empirical studies of immigrant involvement in crime. We conclude with a review of public opinion about immigrants, especially as it relates to immigrants and crime, and then provide original data on the connection between public opinion and immigrant crime.